Sentiment Analysis on NU Online Using KNN Method Important Findings of the Article - Mas Nurul Hamidah; Fardanto Setyatama; R Dimas Adityo; Rahmawati Febrifyaning Tias (Universitas Panca Marga, 2025)
The large population of Indonesia results in the rapid growth of the mobile economy very quickly, Business of Apps in January 2025 states that more than 200 million Indonesians spend an average of 5.7 hours per day in using cell phones or applications contained on cell phones. One of the applications on PlayStore is NU Online with more than 1 million downloads and there are 27 thousand user reviews with an average rating of 4.8. NU Online App was created by one of the largest organizations in Indonesia, Nahdlatul Ulama, the purpose of making the application is to provide convenience to users, especially among pesantren and NU members. Data Mining is the process of finding patterns, trends, and useful information from large amounts of data. One of the algorithms in data mining is KNN. This research focuses on sentiment analysis on the NU Online application to find out that the review is worth POSITIVE, and NEGATIVE using the KNN method, resulting in 72% showing positive sentiment, 28% showing negative sentiment, this shows the performance and performance of the NU Online love application is very good with the support of the highest accuracy evaluation value at K10 which is 0.83.